Evaluation of two strategies for reducing the spread of Salmonella in commercial swine herds during the finishing phase and their incremental cost-effectiveness ratios - Costa, Eduardo de Freitas; Kich, Jalusa Deon; Miele, Marcelo; Morés, Nelson; Amaral, Armando; Coldebella, Arlei; Cardoso, Marisa; Corbellini, Luis Gustavo (Semina: Ciências Agrárias, 2020)
To achieve control of Salmonella contamination in pig carcasses, on-farm measures need to be better understood. Complementary strategies require research not only on their effectiveness but also on their financial impact. In this study, we evaluated the incremental cost-effectiveness ratio of two treatments for reducing Salmonella seroprevalence in commercial swine herds. Pigs treated with a prebiotic or a vaccine were studied and compared with pigs in an untreated control group. Each strategy was applied to three batches of pigs in a commercial integration system; the animals were followed from farrowing to the slaughterhouse, and their serologies upon arrival at finishing farms and before slaughter were evaluated. Additionally, carcass surface contamination was assessed for each strategy. The seroprevalence upon arrival at the finishing farm was lower than 3% in all groups. In the control and vaccine groups, the seroprevalence increased by more than 90 percentage points from the day of arrival at the finishing farm to four days before slaughter. Only the prebiotic treatment yielded a significant effect on preslaughter seroprevalence (a 49 percentage points reduction from that in the control). Carcass contamination was 0% in the prebiotic group, 18.33% in the control group and 29.16% in the vaccine group. Only prebiotics significantly reduced the seroprevalence of Salmonella in the studied herds, and the incremental cost-effectiveness ratio associated with prebiotic use was 1.92 USD to reduce seroprevalence by 10 percentage points per carcass ton.